COMPETENCY - BASED APPROACH TO EFFECTIVE PERFORMANCE OF FUTURE COMPETENT AND CREATIVE TRANSLATORS OF PROFESSIONALLY ORIENTED TEXTS - Yelena V. Gakova; Eleonora K. Nikitina (European Scientific Journal, ESJ, 2014)
Modern world develops very quickly. Changes in people’s lives and technologies occur today much quicker than it was 50 years ago, flows of scientific information in foreign languages scatter in all ends of the world in only a few seconds, therefore, there is a need for a new formation of professionals capable to think and operate according to the new time. Thus, with increase in contacts of Russian scientists and businessmen with foreign partners and taking into account all said above the question of vocational training of translators of professionally oriented texts (scientific and technical texts) is now actual more than ever. The article describes the use of competence – based approach in vocational training and tries to define concepts of «competence» and «competences» of a translator of professionally oriented texts. In the article the necessity to use competency – based approach is outlined in the course of vocational training as it manifests further effective professional performance. The researchers also define «competencies» of a creative translator of professionally oriented texts. In the carried-out analysis of scientific literature and taking into account the teaching experience the authors enumerate the main competences and competencies defining effective performance of a translator of professionally oriented texts.